Responses of photosystem to long-term light stress in a typically shade-tolerant species Panax notoginseng - Cun, Zhu; Xu, Xiang-Zeng; Zhang, Jin-Yan; Shuang, Sheng-Pu; Wu, Hong-Min; An, Tong-Xin; Chen, Jun-Wen (Frontiers in Plant Science, 2023)
Photosynthetic adaptive strategies vary with the growth irradiance. The potential photosynthetic adaptive strategies of shade-tolerant species Panax notoginseng (Burkill) F. H. Chen to long-term high light and low light remains unclear. Photosynthetic performance, photosynthesis-related pigments, leaves anatomical characteristics and antioxidant enzyme activities were comparatively determined in P. notoginseng grown under different light regimes. The thickness of the upper epidermis, palisade tissue, and lower epidermis were declined with increasing growth irradiance. Low-light-grown leaves were declined in transpiration rate (Tr) and stomatal conductance (Cond), but intercellular CO2 concentration (Ci) and net photosynthesis rate (Pn) had opposite trends. The maximum photo-oxidation P700+ (Pm) was greatly reduced in 29.8% full sunlight (FL) plants; The maximum quantum yield of photosystem II (Fv/Fm) in 0.2% FL plants was significantly lowest. Electron transport, thermal dissipation, and the effective quantum yield of PSI [Y(I)] and PSII [Y(II)] were declined in low-light-grown plants compared with high-light-grown P. notoginseng. The minimum value of non-regulated energy dissipation of PSII [Y(NO)] was recorded in 0.2% FL P. notoginseng. OJIP kinetic curve showed that relative variable fluorescence at J-phase (VJ) and the ratio of variable fluorescent FK occupying the FJ-FO amplitude (Wk) were significantly increased in 0.2% FL plants. However, the increase in Wk was lower than the increase in VJ. In conclusion, PSI photoinhibition is the underlying sensitivity of the typically shade-tolerant species P. notoginseng to high light, and the photodamage to PSII acceptor side might cause the typically shade-tolerant plants to be unsuitable for long-term low light stress.